Simultaneous Complement Response via Lectin Pathway in Retina and Optic Nerve in an Experimental Autoimmune Glaucoma Model - Reinehr, Sabrina; Reinhard, Jacqueline; Gandej, Marcel; Kuehn, Sandra; Noristani, Rozina; Faissner, Andreas; Burkhard Dick, H.; Joachim, Stephanie C. (Frontiers in Cellular Neuroscience, 2016)
Glaucoma is a multifactorial disease and especially mechanisms occurring independently from an elevated intraocular pressure (IOP) are still unknown. Likely, the immune system contributes to the glaucoma pathogenesis. Previously, IgG antibody depositions and retinal ganglion cell (RGC) loss were found in an IOP-independent autoimmune glaucoma model. Therefore, we investigated the possible participation of the complement system in this model. Here, rats were immunized with bovine optic nerve homogenate antigen (ONA), while controls (Co) received sodium chloride (n=5-6/group). After 14 days, RGC density was quantified on flatmounts. No changes in the number of RGCs could be observed at this point in time. Longitudinal optic nerve sections were stained against the myelin basic protein (MBP). We could note few signs of degeneration processes. In order to detect distinct complement components, retinas and optic nerves were labeled with complement markers at 3, 7, 14, and 28 days and analyzed. Significantly more C3 and MAC depositions were found in retinas and optic nerves of the ONA group. These were already present at day 7, before RGC loss and demyelination occurred. Additionally, an upregulation of C3 protein was noted via Western Blot at this time. After 14 days, quantitative real-time PCR revealed significant more C3 mRNA in the ONA retinas. An upregulation of the lectin pathway associated mannose-serine-protease-2 (MASP2) was observed in the retinas as well as in the optic nerves of the ONA group after 7 days. Significant more MASP2 in retinas could also be observed via Western Blot analyses at this point in time. No effect was noted in regard to C1q. Therefore, we assume that the immunization led to an activation of the complement system via the lectin pathway in retinas and optic nerves at an early stage in this glaucoma model. This activation seems to be an early response, which then triggers degeneration. These findings can help to develop novel therapy strategies for glaucoma patients.